Single systemic transfer of a human gene associated with exceptional longevity halts the progression of atherosclerosis and inflammation in ApoE knockout mice through a CXCR4-mediated mechanism. (10th July 2019) - Puca, Annibale Alessandro; Carrizzo, Albino; Spinelli, Chiara; Damato, Antonio; Ambrosio, Mariateresa; Villa, Francesco; Ferrario, Anna; Maciag, Anna; Fornai, Francesco; Lenzi, Paola; Valenti, Valentina; di Nonno, Flavio; et al.
Abstract: Aims: Here, we aimed to determine the therapeutic effect of longevity-associated variant ( LAV )-BPIFB4 gene therapy on atherosclerosis. Methods and results: ApoE knockout mice (ApoE −/− ) fed a high-fat diet were randomly allocated to receive LAV-BPIFB4, wild-type ( WT )- BPIFB4, or empty vector via adeno-associated viral vector injection. The primary endpoints of the study were to assess (i) vascular reactivity and (ii) atherosclerotic disease severity, by Echo-Doppler imaging, histology and ultrastructural analysis. Moreover, we assessed the capacity of the LAV-BPIFB4 protein to shift monocyte-derived macrophages of atherosclerotic mice and patients towards an anti-inflammatory phenotype. LAV-BPIFB4 gene therapy rescued endothelial function of mesenteric and femoral arteries from ApoE −/− mice; this effect was blunted by AMD3100, a CXC chemokine receptor type 4 (CXCR4) inhibitor. LAV - BPIFB4 -treated mice showed a CXCR4-mediated shift in the balance between Ly6C high /Ly6C low monocytes and M2/M1 macrophages, along with decreased T cell proliferation and elevated circulating levels of interleukins IL-23 and IL-27. In vitro conditioning with LAV-BPIFB4 protein of macrophages from atherosclerotic patients resulted in a CXCR4-dependent M2 polarization phenotype. Furthermore, LAV-BPIFB4 treatment of arteries explanted from atherosclerotic patients increased the release of atheroprotective IL-33, while inhibiting the release of pro-inflammatory IL-1β, inducing endothelial nitric oxide synthase phosphorylation and restoring endothelial function. Finally, significantly lower plasma BPIFB4 was detected in patients with pathological carotid stenosis (>25%) and intima media thickness >2 mm. Conclusion: Transfer of the LAV of BPIFB4 reduces the atherogenic process and skews macrophages towards an M2-resolving phenotype through modulation of CXCR4, thus opening up novel therapeutic possibilities in cardiovascular disease.